2020
DOI: 10.1002/jmv.26561
|View full text |Cite
|
Sign up to set email alerts
|

A bioinformatic prediction of antigen presentation from SARS‐CoV‐2 spike protein revealed a theoretical correlation of HLA‐DRB1*01 with COVID‐19 fatality in Mexican population: An ecological approach

Abstract: SARS‐CoV‐2 infection is causing a pandemic disease that is reflected in challenging public health problems worldwide. HLA‐based epitope prediction and its association with disease outcomes provide an important base for treatment design. A bioinformatic prediction of T cell epitopes and their restricted HLA class I and II alleles was performed to obtain immunogenic epitopes and HLA alleles from the spike protein of the SARS‐CoV‐2 virus. Also, a correlation with the predicted fatality rate of hospitalized patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 40 publications
0
35
1
Order By: Relevance
“…Interestingly, HLA-A*02 alleles, among other class I and II alleles, were also identified as functional molecules for presenting SARS-CoV-2 peptides in a bioinformatic prediction study. In this same last report, an ecological study was also performed, and the HLA-DRB1*01 allele was found associated with COVID-19 fatality in a Mexican population; and, although the authors have addressed several limitations, the result must be taken with caution ( 47 ).…”
Section: Genetic Variants In the Study Of Covid-19 Susceptibility Andmentioning
confidence: 99%
“…Interestingly, HLA-A*02 alleles, among other class I and II alleles, were also identified as functional molecules for presenting SARS-CoV-2 peptides in a bioinformatic prediction study. In this same last report, an ecological study was also performed, and the HLA-DRB1*01 allele was found associated with COVID-19 fatality in a Mexican population; and, although the authors have addressed several limitations, the result must be taken with caution ( 47 ).…”
Section: Genetic Variants In the Study Of Covid-19 Susceptibility Andmentioning
confidence: 99%
“…Like this study, many other investigations have successfully employed bioinformatic tools to predict the epitopic regions of different proteins in SARS-CoV-2/Wuhan. 30,31 However, experimental validations of these predictions are essentially required.…”
Section: Sequencementioning
confidence: 99%
“…In Mexico, a significant negative correlation was found between the frequency of the class II HLA-DRB1*01 allele and the fatality rate in hospitalized patients, based on bioinformatic predictions. This allele can present at least nine epitopes of the M protein and 11 of the N protein, revealing its high relevance for SARS-CoV-2 immunity [151] .…”
Section: Associated Genetic Polymorphisms ( Table 3 )mentioning
confidence: 98%